The Visualization of Spatial Data in the Humanities. - Jessop, Martyn (Literary & Linguistic Computing, 2004)
The visualization and analysis of spatial data can shed new light on the nature and meaning of data throughout the Humanities. However such work is often avoided because it is seen as requiring expensive new hardware and software resources or involving a substantial expenditure of time and effort overcoming a steep learning curve before worthwhile results can be obtained. The Centre for Computing in the Humanities at King's College London collaborates with researchers in a variety of humanities disciplines on a range of projects that often involve a component of spatial data. This has given the Centre an opportunity to explore methods of visualizing, analysing and displaying spatial data in a range of humanities disciplines. This paper discusses some of the intellectual, research and practical issues affecting the use of spatial data in Humanities Computing projects. It is illustrated by examples from a number of projects at King's College. Although it is grounded on specific examples to support the points being made the main aim is to draw out a series of general themes which affect the use of spatial data by researchers throughout the Humanities and increase awareness of what can be achieved with minimal resources and a little creative thought.